The Correlations Among Vocabulary Mastery, Reading Interest And Reading Comprehension of The Eleventh Grade Students of Private Senior High School of Talang Ubi Sub-District of Pali Regency - Safitri, Diana; Simaibang , Baginda; Mulyadi, Mulyadi (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
This thesis is concerned with the inquiry on the correlations among vocabulary mastery, reading interest, and reading comprehension of the eleventh grade students of Private Senior High School of Talang Ubi Sub-District of Pali regency. The total number of the population were 200 students. The sample for this study was 51 students taken through a two-stage random sampling technique. Data were collected by adopting a questionnaire for reading interest and test for vocabulary mastery and reading interest. Data were analyzed by using r-Product Moment and Multiple Regression. The data analysis shows that = 0.774 with =0.599 and p-Value is 0.00. This value is lower than 0.05. This is significant. So, Ha was accepted while Ho was rejected. Conclusions suggested that there are significant correlations among vocabulary mastery, reading interest, and reading comprehension of the eleventh grade students of Senior High School of Talang Ubi Sub-District of Pali Regency.